As relações de poder entre o Estado-nação e as jornadas de junho: horizontes para uma análise da multidão - Graeff, Rodrigo (2020)
This research addressed the state's reaction to the June Protests, seeking to analyze whether such reactions were part of a legitimate act of state sovereignty. Throughout the research, analyses were produced aimed at understanding the set of movements taking place in the 21st century, as well as the June Protests. It also analyzed how the Brazilian nation-state responded to the protests undertaken in the country since June 2013. Finally, the research sought to identify the global power relations that influence and limit the functioning of the nation-state, concluding that the repression of the movements was illegitimate, since it was motivated by the need to maintain its sovereignty in the face of global pressures for security.